The association of pattern of lifetime alcohol use and cause of death in the European Prospective Investigation into Cancer and Nutrition (EPIC) study - Bergmann, Manuela; Teucher, Birgit; Kaaks, Rudolf (International journal of epidemiology, 2013)
Abstract. Background There is limited evidence for an association between the pattern of lifetime alcohol use and cause-specific risk of death.Methods Multivari
Published: 08 January 2014
Gesehen am 24.11.2020